Living with ME and chronic fatigue syndrome - Coakley, Gerald; Knops, Beverly (London : Penguin Life, 2022)
Chronic fatigue conditions are some of the most frustrating, life-altering and stigmatized illnesses, so why are they still so poorly understood? ME/CFS affects roughly 17 million people worldwide. Medicalscience still cannot explain why some people get chronic fatigue syndromes and, distressingly, there are few effective treatments. While many people with ME/CFS are able to live a fairly normal life, a significant minority have symptoms so severe that they are confined to their house, or even their bed, and suicide rates are well above the national average. Living with ME and Chronic Fatigue Syndrome, by consultant rheumatologist Dr Gerald Coakley and occupational therapist Beverly Knops, is a much-needed, evidence-based guide for people struggling with ME/CFS - as well as their friends and family - that provides practical information and accessible advice on how to manage and live with this challenging condition, at all stages of severity. It will explore: - The causes and management options for ME/CFS - The impact of the condition on work, education and emotional wellbeing - The importance of a balanced, nutritious diet in managing your symptoms - Post-Viral Fatigue Syndrome (PVFS) and other fatigue-related syndromes - Advice for carers and questions to ask your doctor - Life after ME/CFS This essential, concise book, and its empowering patient stories of hope, will equip readers with the knowledge, strategies and support to navigate and manage this challenging condition.
Description based on CIP data; resource not viewed.
Keywords: Myalgic encephalomyelitis -- Patients; Myalgic encephalomyelitis -- Popular works; x; v; Electronic books; Popular works